2017
DOI: 10.1080/09537104.2016.1257783
|View full text |Cite
|
Sign up to set email alerts
|

Progress in bio-manufacture of platelets for transfusion

Abstract: Blood transfusion services face an ever-increasing demand for donor platelets to meet clinical needs. Whilst strategies for increasing platelet storage life and improving the efficiency of donor platelet collection are important, in the longer term, platelets generated by bio-manufacturing processes will be required to meet demands. Production of sufficient numbers of in vitro-derived platelets for transfusion represents a significant bioengineering challenge. In this review, we highlight recent progress in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…In fact, several studies reported enhanced PLT shedding in the presence of shear force, which mimics the blood stream, generated in a small flow chamber . More recently, the development of complex bioreactor systems, which reproduce not only the shear stresses but also the bone marrow perivascular space, showed higher PLT production efficiency reaching a yield of 100–150 PLTs/MK . Consequently, a combination of these innovative technologies with BC as source of HPCs may represent an enormous straight forward step towards in vitro PLT production for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies reported enhanced PLT shedding in the presence of shear force, which mimics the blood stream, generated in a small flow chamber . More recently, the development of complex bioreactor systems, which reproduce not only the shear stresses but also the bone marrow perivascular space, showed higher PLT production efficiency reaching a yield of 100–150 PLTs/MK . Consequently, a combination of these innovative technologies with BC as source of HPCs may represent an enormous straight forward step towards in vitro PLT production for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Yields of PLT production may profit in the future from the harmonization of MK expansion and differentiation culture systems towards a synchronized PLT formation and release [74]. The application of shear stress in the designed bioreactor aimed to provide a physical cue to induce a synchronized proPLT formation, extension, and PLT release [80]. However, it remains highly desirable to identify biological or chemical signals that might support this process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, imMKCLs, produced as discussed earlier in this review [49], from voluntary blood component donors with specific HLA haplotypes are currently being tested in a clinical phase I trial in Japan, initiated by Koji Eto [79]. The group demonstrated an approach for generation of 0.5 × 10 11 imMKCL-derived PLTs from each batch of an 8-liter culture [80]. The imMKCLs are analyzed for their PLT production capacity in vivo, determining their suitability in transfusion therapy.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Due to the limited availability of HSCs, further studies on iPSCs have been undertaken. Over the past years, iPSCs have shown great potential in biomedical research (38,39).…”
Section: Stem Cell Sourcesmentioning
confidence: 99%